Islamic Financial Inclusion: A Review and Bibliometric Analysis - Puspita, Amelia Tri; Kassim, Siti Fatimah Mohd (SMART Insight, 2024)
Inclusive finance is very relevant to support the effectiveness of the functions and duties of the central bank and national banking both in terms of monetary, payment system and macroprudential. Inclusive finance has multidimensional indicators, namely indicators of accessibility, availability and usage of banking services. Islamic banking as part of the national banking industry, with its special characteristics also has great potential to contribute to realizing national financial inclusiveness. This study aims to determine the development of Islamic financial inclusion research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 130 indexed research publications. The data is then processed and analyzed using the VoS viewer application to determine the bibliometric map of Islamic financial inclusion research development. There are at least 4 clusters of research maps related to Islamic financial inclusion, namely: (1) Digitalization Challenges in Islamic Financial Inclusion, (2) Islamic Financial Inclusion and Economic Growth, (3) Financial Inclusion and Islamic Financial Products, and (4) Financial Stability and Islamic Financial Inclusion.